2020
DOI: 10.3389/fmicb.2020.610650
|View full text |Cite
|
Sign up to set email alerts
|

MogR Is a Ubiquitous Transcriptional Repressor Affecting Motility, Biofilm Formation and Virulence in Bacillus thuringiensis

Abstract: Flagellar motility is considered an important virulence factor in different pathogenic bacteria. In Listeria monocytogenes the transcriptional repressor MogR regulates motility in a temperature-dependent manner, directly repressing flagellar- and chemotaxis genes. The only other bacteria known to carry a mogR homolog are members of the Bacillus cereus group, which includes motile species such as B. cereus and Bacillus thuringiensis as well as the non-motile species Bacillus anthracis, Bacillus mycoides and Bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 101 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…NaCl may act as a chemical cue for B. subtilis cells to enhance motility, which may provide competitive benefits in nature. Importantly, how chemicals typically encountered by bacterial cells in their environment influences the multicellular systems is less understood (45). Various chemicals have distinct effects on the ability of bacterial species to form biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…NaCl may act as a chemical cue for B. subtilis cells to enhance motility, which may provide competitive benefits in nature. Importantly, how chemicals typically encountered by bacterial cells in their environment influences the multicellular systems is less understood (45). Various chemicals have distinct effects on the ability of bacterial species to form biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA-Seq analysis showed that the motility genes were down-regulated in 7 dpi bacteria compared to in-vitro -grown cells, and that the motility repressor-encoding gene mogR [32] was up-regulated in 7 dpi bacteria compared to exponentially growing cells. Similarly, the biofilm-associated genes calY , tasA and the eps2 locus [33, 34], were up-regulated compared to exponentially growing cells.…”
Section: Discussionmentioning
confidence: 99%
“…That biofilm formation and motility are reciprocally regulated by the second messenger c-di-GMP is widely accepted not only in B. cereus group bacteria, but also in a number of other species [ [33] , [34] , [35] , [36] ]. However, a recent study showed that in B. thuringiensis , overexpression of MogR, a homolog of the transcriptional repressor MogR in Listeria monocytogenes , led to non-motile cells and a substantial increase in biofilm formation [ 37 ]. These results imply intimate cross-regulatory connections between motility and biofilm formation.…”
Section: Global Analysis Of Biofilm Developmentmentioning
confidence: 99%